2018
DOI: 10.1088/1367-2630/aad997
|View full text |Cite
|
Sign up to set email alerts
|

Lithographically engineered shallow nitrogen-vacancy centers in diamond for external nuclear spin sensing

Abstract: The simultaneous control of the number and position of negatively charged nitrogen-vacancy (NV) centers in diamond was achieved. While single near-surface NV centers are known to exhibit outstanding capabilities in external spin sensing, trade-off relationships among the accuracy of the number and position, and the coherence of NV centers have made the use of such engineered NV centers difficult. Namely, low-energy nitrogen implantation with lithographic techniques enables the nanoscale position control but re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 41 publications
3
34
1
Order By: Relevance
“…In 2005, in-plane targeting was achieved via focusing ion beam implantation 1619 , while a beam diameter of 100 nm was achieved in 2013 16 in mask-less implantation using a focused ion beam. The collimated ion implantation via nanometre-sized hole gives a much higher positioning resolution 2029 . For example, Toyli et al demonstrated the fine grid of NV centres by nitrogen implantation via a nanohole in 2010 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, in-plane targeting was achieved via focusing ion beam implantation 1619 , while a beam diameter of 100 nm was achieved in 2013 16 in mask-less implantation using a focused ion beam. The collimated ion implantation via nanometre-sized hole gives a much higher positioning resolution 2029 . For example, Toyli et al demonstrated the fine grid of NV centres by nitrogen implantation via a nanohole in 2010 23 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still room to improve the separation distance and coherence time owing to fabricate coherently coupled NV centres by this technique. The implantation via a nanohole on a poly (methyl methacrylate) (PMMA) resist mask fabricated by electron beam lithography is commonly utilized for accurately positioning NV centres as of today 2429 . The in-plane accuracy is determined by the nanohole diameter as well as by straggling.…”
Section: Introductionmentioning
confidence: 99%
“…We conjecture thermal and electrical drifts as well as mechanical vibrations as major source of beam pointing fluctuations. d) Focus spot determination of nitrogen molecular ions yielding σ = 121 (35) nm in x-direction. The measuring time for the extraction of 289 nitrogen ions takes about 117 min, which results in a loading rate of 2.5 ions/min.…”
Section: Sample Preparation and Implantationmentioning
confidence: 99%
“…However, these approaches require a sophisticated fabrication process for materials with high hardness such as diamond, and the nanoscale devices often aggravate decoherence of optical and spin qubits [17][18][19]. Furthermore, to precisely couple the defects with photonic structures at the maximum optical mode, the lithography with patterned masks or siteselective generation of defects are required [20,21].…”
Section: Introductionmentioning
confidence: 99%